2013
DOI: 10.1097/igc.0b013e3182798188
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Immunohistochemical Staining as a Prognostic Indicator in Uterine Serous Carcinoma

Abstract: Our study illustrates that a low level of BRCA1 protein expression is a favorable prognostic indicator in USC, similar to what is observed in high-grade serous ovarian carcinoma. Further studies should focus on the BRCA1 status of USCs at a molecular level and also investigate whether BRCA1 protein expression is associated with response to chemotherapy in USC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Some groups have suggested that patients with BRCA1 or BRCA2 germline mutations may be at increased risk of developing uterine serous carcinomas . Research from our own group has definitively shown that a low level of BRCA1 immunohistochemistry is a favourable prognostic indicator in serous cancers of the endometrium, similar to what is seen in high grade serous fallopian tube/ovarian carcinoma …”
Section: The Fanconi Anaemia‐brca Pathway and Hereditary Breast‐ovarimentioning
confidence: 75%
See 3 more Smart Citations
“…Some groups have suggested that patients with BRCA1 or BRCA2 germline mutations may be at increased risk of developing uterine serous carcinomas . Research from our own group has definitively shown that a low level of BRCA1 immunohistochemistry is a favourable prognostic indicator in serous cancers of the endometrium, similar to what is seen in high grade serous fallopian tube/ovarian carcinoma …”
Section: The Fanconi Anaemia‐brca Pathway and Hereditary Breast‐ovarimentioning
confidence: 75%
“…Uterine serous carcinomas are morphologically virtually identical to their high grade serous fallopian tube/ovarian counterparts. 34 However, there remains some debate about the association of germline BRCA mutations and serous carcinoma of the endometrium. This area remains significantly underinvestigated with most studies suggesting that there is no association with BRCA mutation.…”
Section: Endometrial Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…31 BRCA1 staining was performed using the mouse anti-BRCA1 (AB-1) mouse monoclonal (MS110) antibody (Calbiochem, UK) at a 1:200 dilution as previously described. 14,41 Evaluation of BRCA1 and MAD2 Immunostaining Three BRCA1-and MAD2-stained slides (which were derived from 2 immediately adjacent tissue sections of the TMA) were scored independently by 3 observers (T.B., L.N., and W.G.M.). Only cores containing greater than 20% tumor were scored.…”
Section: Immunohistochemistrymentioning
confidence: 99%